BT-4 The treatment history of long-term survivors of Optic Pathway Glioma in Kobe Children's Hospital. (6th December 2021) - Kawamura, Atsufumi; Koyama, Junji; Akutsu, Nobuyuki; Higashino, Masashi; Fujita, Kenji
Abstract: Optic pathway glioma(OPG) is almost recognized in childhood and about 0.01–0.02% of whole brain tumor in Japan. Because of the rare tumor, there are few reports about results of its treatment. In 2021, Guideline of Optic pathway/hypothalamic glioma is indicated from The japan Society for Neuro-Oncology. We retrospectively study 9 cases history of OPG who have treated for more than 5 years from January 2005 to March 2021 in Kobe Children's Hospital. Cases are 4 boys and 5 girls. Average age at diagnosis is 3.8 years old and average follow up term is 11 years 10 months. They are 4 Pilocytic astrocytoma, 3 Pilomyxoid astrocytoma, and 1 Fibrillary astrocytoma. Al l cases have survived. There are only 2 cases who could be controlled with single series of surgical treatment and chemotherapy. Most cases need several times of resection and chemotherapy and uncontrollable 5 cases required radiological treatment. 2 cases are still under treatment for over 10 years. For OPG, partial resection to control hydrocephalus is recommended and several trial of chemotherapy must be carried out. There exist a few cases who need continuous treatment for long term. The other side, a few cases are uncontrollable those need radiotherapy to manage tumor volume. Because the history of OPG would be long term, we should adjust the treatment plan to environment of patients.